2023
DOI: 10.1159/000534962
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mindfulness for Youth (MYmind) versus Group Cognitive Behavioral Therapy in Improving Attention and Reducing Behavioral Problems among Children with Attention-Deficit Hyperactivity Disorder and Their Parents: A Randomized Controlled Trial

Samuel Yeung Shan Wong,
Stanley Kam Chung Chan,
Benjamin Hon Kei Yip
et al.

Abstract: <b><i>Introduction:</i></b> There is a lack of studies evaluating mindfulness-based interventions for children with attention-deficit hyperactivity disorder (ADHD) compared with an evidence-based control. This randomized controlled trial (RCT) evaluated the effects of mindfulness for youth (MYmind) in improving children’s attention, behavior, and parent-related outcomes versus cognitive behavioral therapy (CBT). <b><i>Methods:</i></b> A total of 138 families of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…Primary and secondary outcomes included children's attention, ADHD-related symptoms, behaviours, executive function, and mindfulness levels as well as parental stress, parenting styles, and parent's own ADHD-related symptoms and wellbeing (Chan et al, 2018). Results showed that both programs significantly improved children's attention and most other outcomes, with no difference in effectiveness between the CBT and the family mindfulness program up to the 6-month follow-up assessment (Wong et al, 2023).…”
mentioning
confidence: 99%
“…Primary and secondary outcomes included children's attention, ADHD-related symptoms, behaviours, executive function, and mindfulness levels as well as parental stress, parenting styles, and parent's own ADHD-related symptoms and wellbeing (Chan et al, 2018). Results showed that both programs significantly improved children's attention and most other outcomes, with no difference in effectiveness between the CBT and the family mindfulness program up to the 6-month follow-up assessment (Wong et al, 2023).…”
mentioning
confidence: 99%